Ultrasound radiomics-based machine learning models for risk stratification of follicular thyroid tumors - Yuan, Ya; Wang, Xinyue; Deng, Hongyan; Cao, Kunpeng; Yu, Fei (Frontiers in Oncology, 2026)
BackgroundFollicular thyroid carcinoma (FTC) is the second most common malignant thyroid tumor. Preoperative differentiation among follicular thyroid adenoma (FA), follicular tumor of uncertain malignant potential (FT-UMP), and FTC remains challenging using conventional ultrasound and fine-needle aspiration. This study aims to develop a machine learning model utilizing ultrasound radiomic features to improve risk stratification of follicular thyroid tumors.MethodsA total of 277 patients with histopathologically confirmed follicular tumors (163 FA, 63 FT-UMP, 51 FTC) were included. Clinical and ultrasound features, along with radiomic features from intratumoral and peritumoral regions, were extracted from preoperative ultrasound images. Three machine learning models—logistic regression (LR), support vector machine (SVM), and random forest (RF)—were trained to construct four models: clinical-ultrasound (U), clinical-ultrasound with intratumoral radiomics (UI), clinical-ultrasound with peritumoral radiomics (UP), and clinical-ultrasound with combined intratumoral and peritumoral radiomics (UIP).ResultsThe RF-based clinical-ultrasound model demonstrated the highest accuracy (test: 0.643) but exhibited significant overfitting in radiomics-based models. The SVM model showed moderate performance. The LR model in the UP and UIP models delivered stable performance, achieving the highest test accuracy of 0.643. Specifically, the UP model showed improved micro-AUC, specificity, negative predictive value (NPV), and F1 score. The LR model exhibited high sensitivity but low specificity for benign nodules, and high specificity but low sensitivity for malignant nodules. All models performed poorly in identifying FT-UMP nodules.ConclusionIntegrating peritumoral radiomic features with clinical-ultrasound features using logistic regression enhances the differentiation between benign and malignant follicular thyroid tumors.